Analysis of the Influence of Job Effort, Job Insecurity, Task-Oriented Leadership on Work Performance and Organizational Commitment During the Covid 19 Pandemic Recovery Period in Indonesia - Siswanto, Agus; Setiawan, Zunan (Politeknik APP Jakarta, 2024)
The aim of the study was to analyze and examine the effect of job effort, job insecurity, task-oriented leadership on job performance and organizational commitment. Using the Partial Least Squares Structural Equation Modeling Method (PLS-SEM). This research involved hotel employee respondents from various big cities in Indonesia. Data was collected through an online survey that used a questionnaire that had been tested for validity and reliability. The results of the PLS-SEM analysis show that job effort has a positive and significant effect on job performance. Job insecurity is proven to have a negative and significant effect on job performance. Meanwhile, job effort and task-oriented leadership are proven to have a positive and significant influence on organizational commitment. However, job insecurity is not proven to have a significant effect on organizational commitment. The results of this study can be used as a guide for managers and organizational leaders in designing strategies to improve employee performance and commitment amid the recovery situation from the Covid-19 pandemic in Indonesia.